Validation and Prediction of the School Psychological Capital Among Chinese College Students - Kang, Xia; Wu, Yajun; Li, Lisheng (Frontiers in Psychology, 2021)
This study validated the school Psychological Captial (PsyCap) scale in the Chinese context and examined the predictive effect of PsyCap resources on academic engagement and achievement emotions. Self-report data for PsyCap resources, student engagement, enjoyment, anxiety, and boredom toward English learning were collected from 1000 sophomores. Item level analyses and confirmatory factor analysis were used to verify the validity of the school PsyCap scale, and structural equation modeling was applied to reveal the predictive effect of school PsyCap resources on academic engagement and achievement emotions. Results showed that the school PsyCap scale retained superior psychometric properties. Besides, PsyCap resources were demonstrated to have a positive relationship to academic engagement and enjoyment, and a negative relationship to anxiety and boredom. The effectiveness of the school PsyCap scale was verified among Chinese college students and besides the traditional predictors, school PsyCap is also critically important for students’ academic engagement and achievement emotions. Limitations and implications are discussed.